SAT0241 Early response to belimumab in sle-related joint involvement evaluated by ultrasonographic assessment. (15th June 2017) - Massaro, L; Ceccarelli, F; Spinelli, FR; Morello, F; Perricone, C; Miranda, F; Truglia, S; Orefice, V; Rutigliano, IM; Alessandri, C; Valesini, G; Conti, F
Abstract : Background: Belimumab (BLM), a fully human monoclonal antibody directed against B lymphocyte stimulator (BLyS), is currently the only biological drug approved for the treatment of active Systemic Lupus erythematosus (SLE) patients not responding to standard of care. Data from RCTs and observational studies have demonstrated its efficacy, especially in patients with joint involvement. Focusing on this specific manifestation, the response has been also demonstrated by using Disease Activity Score on 28 joints (DAS28) (1). No data are available about the response to BLM in terms of synovitis, assessed by ultrasonography (US). Objectives: In the present 6-months longitudinal study, we evaluated the response to BLM in SLE patients treated for joint involvement, by using clinimetric indices and US assessment. Methods: SLE patients starting BLM in the period between August 2013 and December 2016 were prospectively examined. The present analysis was restricted to patients requiring BLM for joint involvement. A complete physical examination and US assessment were performed at baseline (T0) and after 3 (T3) and 6 months (T6). At each time, we assessed the global disease activity by Systemic Lupus Erythematosus Disease Activity Index-2000 (SLEDAI-2K) and the joint involvement activity by DAS28. US evaluation of 12 joints (I-V metacarpophalangeal, I-V proximal interphalangeal, wrist and knee bilateral) was performed to identify inflammatory features (synovial effusion and hypertrophy, power Doppler) according to the OMERACT definitions. These elementary lesions were scored according to a semi-quantitative scale (0=absent, 1=mild, 2=moderate and 3=severe) and a total score, corresponding to the patient's inflammatory status (0–216) was obtained by their sum. Results: Moving from 35 SLE patients starting BLM, 14 (14 female; mean age±SD 48.4±8.6 years; mean disease duration±SD 255.4±124.2 months) were treated for prevalent joint involvement. At baseline, the mean DAS28±SD was 4.5±1.1, the mean SLEDAI-2K±SD was 6.1±1.5 and the mean daily prednisone±SD was 7.8±3.5 mg. After 3 months of treatment we observed a significant reduction in mean DAS28 (3.1±0.8 vs 4.5±1.1, P=0.007) and in mean SLEDAI-2K (3.5±2.1 vs 6.1±1.5, P=0.003) compared to baseline. The mean daily prednisone significantly decreased at T6 (4.7±1.4 vs 7.8±3.5 mg, P=0.03) while the rest of the therapy remained stable for 6 months. Of note, the mean total US score significantly decreased at T3 compared to T0 (13.7±24.4 vs 22.2±22.6, P=0.001). This result was maintained in 12 patients (85.7%) after 6 months with a statistically significant difference compared to T0 (7.9±6.6 vs 22.2±22.6, P=0.003) (Figure 1 ). Conclusions: The results of the present study demonstrated the efficacy of BLM in SLE-related joint involvement, evaluated by SLEDAI-2K and DAS28, confirming previous data reported in the scientific literature. For the first time, we demonstrated an early response to BLM as proved by the reduction of the total US synovitis score after 3 months, reflecting the improvement of the joint inflammatory status. References: Iaccarino L et al. Effects of Belimumab on Flare Rate and Expected Damage Progression in Patients With Active Systemic Lupus Erythematosus. Arthritis Care Res. 2017; 69:115–123. Disclosure of Interest: None declared